Efektifitas Kehadiran Mahasiswa KKN MBKM Program Studi Pendidikan Sosiologi UNIMA dalam Membantu Kinerja Pemerintah Kelurahan Rurukan, Kecamatan Tomohon Timur - Salem, Veronike E.T; Mesra, Romi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
As a form of community service, KKN functions to assist the community in solving problems faced by the community on a daily basis, ranging from small problems to complex problems that occur in society and is also very useful as a student learning process in the realities of society. The method used is qualitative research by collecting observation data and direct interviews with several informants. The general results of the research show how effective the KKN MBKM students are in assisting the performance of the kelurahan government, namely KKN students helping to make letters, both business letters, loss letters, letters, heirs and recording the names of toddlers and the elderly, and helping village officials to distributing groceries to the elderly.